Civil society participation in global governance: Insights from climate politics. (14th March 2013) - Böhmelt, Tobias; Koubi, Vally; Bernauer, Thomas
Abstract A rather unique feature of global climate negotiations is that most governments allow representatives of civil society organisations to be part of their national delegation. It remains unclear, however, why states grant such access in the first place. While there are likely to be benefits from formally including civil society, there are also substantial costs stemming from constraints on sovereignty. In light of this tradeoff, this article argues for a 'contagion' effect that explains this phenomenon besides domestic determinants. In particular, states, which are more central to the broader network of global governance, are more likely to be informed of and influenced by other states' actions and policies toward civil society. In turn, more central governments are likely to include civil society actors if other governments do so as well. This argument is tested with data on the participation of civil society organisations in national delegations to global climate negotiations between 1995 and 2005. To further uncover the underlying mechanisms, the article also provides an analysis of survey data collected at the United Nations Framework Convention on Climate Change (UNFCCC) negotiations in Durban in 2011.